DAMPAK HAMBATAN DISLEKSIA PADA SELF-ESTEEM SISWA DI SEKOLAH DASAR INKLUSI - Dhani Kusumawardana; Tita Rosita (COLLASE (Creative of Learning Students Elementary Education), 2021)
The purpose of this study was to determine the impact of the barriers of dyslexia on the self-esteem of students in Inclusive Primary Schools. The study was conducted at one of the private elementary schools in Bandung, while the research subjects were the 4th-grade students who have dyslexic obstacles. The research method used was case study which is a descriptive qualitative method. Data collection was carried out using interviews and observation methods.  Based on observations of the students and interviews with the homeroom teachers, the research concludes that the impact of dyslexia on self-esteem on the competence and power aspects depicts a low-level of self-esteem, but on the significance and virtue aspects, it depicts a high-level self-esteem.